Micronutrient adequacy of pediatric patients on enteral nutritional therapy during hospitalization - Chaves, Anna Beatriz; Irber, Ioná; Haack, Adriana; Horino, Aline (Revista JRG de Estudos Acadêmicos, 2025)
Background: Childhood is a critical step in developing and growing, not yet physically but mentally and immunologically. In the hospitalization context, a correct, adequate, and complete nutritional apport is extremely important for optimization of treatment. In this context, this research aims to evaluate the nutritional adequacy of patients admitted to the Maternal and Child Hospital of Brasília who are on full enteral exclusive nutritional therapy. Methods: That’s a quantitative research in which the participants were patients between 0 and 14 years of age during the medical hospitalization and that were using an exclusive enteral feeding tube with the diet equal to the final nutritional goal planned. The data were taken from the electronic medical record and the prevalence of each micronutrient was calculated and for adequation was considered a percentage between 90% to 110%. This research was approved by the research ethics committee. Results: 117 patients were chosen, most are male, between 0 to 6 months, and have the principal hospitalization diagnostic of a respiratory disease. The prevalence of adequacy of micronutrients shows that sodium and potassium are nutrients with lower adequacy, vitamin A is the most adequate, and the upper limit recommended for some nutrients was surpassed. Conclusion: This research showed that dietary recommendations for micronutrients are not completely respected for pediatric patients who are on full enteral exclusive nutritional therapy with the diet equal to the final nutritional goal planned. This intake out of references to micronutrients may be posing health risks for this group and this demonstrates the need to investigate the cause and the consequence of this intaking profile. To transform this, a law revision is necessary, supported by more studies and researches about the micronutrients adequation in the pediatric context, finding to establish the Brazilian child’s micronutrients recommendations.